2017
DOI: 10.1016/j.lrp.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Management teams' regulatory foci and organizational units' exploratory innovation: The mediating role of coordination mechanisms

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 124 publications
2
40
0
1
Order By: Relevance
“…On the other hand, the technological frames are envisaged as core drivers to facilitate the technological changes in organizations (Orlikowski and Gash, 1994). According to Tuncdogan et al (2016), development of theories regarding the top managers' psychology, organizations innovation and change is still lacking The importance of upper echelons theory is not only emphasized in internationalization process but also in the academic discipline (Dauth et al, 2017), and many studies have elaborated upon the role of the theory in internationalization process (Jaw and Lin, 2009;Thomas and McDaniel, 1990;Tihanyi et al, 2000). Undoubtedly, change in organizations can be brought through the top managements instead of bottom line managers (Heyden et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, the technological frames are envisaged as core drivers to facilitate the technological changes in organizations (Orlikowski and Gash, 1994). According to Tuncdogan et al (2016), development of theories regarding the top managers' psychology, organizations innovation and change is still lacking The importance of upper echelons theory is not only emphasized in internationalization process but also in the academic discipline (Dauth et al, 2017), and many studies have elaborated upon the role of the theory in internationalization process (Jaw and Lin, 2009;Thomas and McDaniel, 1990;Tihanyi et al, 2000). Undoubtedly, change in organizations can be brought through the top managements instead of bottom line managers (Heyden et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus far, research on conflict management has shown more focus on the relationships between conflict-handling style of the leader and team performance (De Dreu & Gelfand, 2008; Prieto-Remón et al, 2015; Rahim, 2002; Tjosvold, 2008; Tjosvold et al, 2001). Alternatively, the relationship between team coordination and team performance has been the focus of a number of prior studies in the management literature (Banks, Pollack, & Seers, 2016; Rico, Sánchez-Manzanares, Gil, & Gibson, 2008; Tuncdogan, Boon, Mom, Bosch, & Volberda, 2017; Yukl, 2006; Zhang et al, 2011 ). Coordination processes involve the activities orchestrating the relationship and scheduling interdependent tasks in the team environment (e.g., managing work, setting up the tasks of each member, and detailing guidelines and regular procedures) (Yukl, 2006; Zalesny, Salas, & Prince, 1995).…”
Section: Conceptual Framework Developmentmentioning
confidence: 99%
“…Coordination processes involve the activities orchestrating the relationship and scheduling interdependent tasks in the team environment (e.g., managing work, setting up the tasks of each member, and detailing guidelines and regular procedures) (Yukl, 2006; Zalesny, Salas, & Prince, 1995). In the same way, coordination activities are observed as necessary conduct for teams to be able to exchange information and straighten the course of team member actions (Marks, Mathieu, & Zaccaro, 2001; Tuncdogan et al, 2017). Even though we are aware of the critical relationship between conflict management and team performance, limited studies have examined the conflict management style of leaders, coordination, and performance together, particularly in multicultural team environments in the construction industry.…”
Section: Conceptual Framework Developmentmentioning
confidence: 99%
“…Although extensively studied at the organizational or business unit level (see O'Reilly & Tushman, 2013), ultimately the decision to explore or exploit has to be made by managers or employees within those organizations (Mom et al, 2009;Van der Borgh & Schepers, 2014). Despite many calls for research (e.g., Gupta et al, 2006;Raisch & Birkinshaw, 2008), there is still relatively little research on how individuals make the exploration-exploitation trade-off (Bonesso et al, 2014;Rosing & Zacher, 2017;Tuncdogan et al, 2017).…”
Section: Accountability and Individual Exploration/exploitationmentioning
confidence: 99%